Repellency of Plant Extracts against the Legume Flower Thrips Megalurothrips sjostedti (Thysanoptera: Thripidae) - Andnet Abtew; Sevgan Subramanian; Xavier Cheseto; Serge Kreiter; Giovanna Tropea Garzia; Thibaud Martin (Insects, 2015)
Megalurothrips sjostedti Trybom is an important pest of cowpea (Vigna unguiculata L.) in Africa. To propose an alternative to chemical control, the repellency of 24 plant extracts was evaluated against adult female thrips of M. sjostedti in the laboratory. Plant extracts in ethanol were separately applied on a filter paper disk in a still air visual cue olfactometer. The results showed highly significant differences in repellency among extract type, concentration and their interactions. We classified the level of repellency into four categories as strong, good, moderate and weak or non- repellent based on hierarchical ascendant classification. We identified Piper nigrum, Cinnamomum zeylanicum, Cinnamomum cassia as strong repellents. Five extracts were classified as good, eight as moderate and the remaining eight extracts were weak or non-repellent. Repellency of the extracts increased with the concentration suggesting that the behavioral response of M. sjostedti was dose-dependent. Mono- and sesquiterpene hydrocarbon compounds from seven highly repellent extracts were identified by gas chromatography-mass spectrometry (GC/MS). The use of repellent extracts could be useful in developing integrated pest management strategies for thrips on legume crops. In this regard, the specific modes of action of the identified compounds need to be investigated to incorporate them into the existing crop protection strategies.